2020
DOI: 10.1021/acs.jpclett.0c01439
|View full text |Cite
|
Sign up to set email alerts
|

On the Theoretical Determination of Photolysis Properties for Atmospheric Volatile Organic Compounds

Abstract: Volatile organic compounds (VOCs) are ubiquitous atmospheric molecules that generate a complex network of chemical reactions in the troposphere, often triggered by the absorption of sunlight. Understanding the VOC composition of the atmosphere relies on our ability to characterize all of their possible reaction pathways. When considering reactions of (transient) VOCs with sunlight, the availability of photolysis rate constants, utilized in general atmospheric models, is often out of experimental reach due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 59 publications
0
57
0
Order By: Relevance
“…For methylhydroperoxide, the 6-311+G* basis set was employed since diffuse basis functions are needed to describe the valence-Rydberg mixing in peroxide excited states. 54 …”
Section: Computational Detailsmentioning
confidence: 99%
“…For methylhydroperoxide, the 6-311+G* basis set was employed since diffuse basis functions are needed to describe the valence-Rydberg mixing in peroxide excited states. 54 …”
Section: Computational Detailsmentioning
confidence: 99%
“…The overarching aim is to devise a simple yet versatile technique for computing the absorption spectra that may be used to calculate the UV absorption spectra of CIs of varying molecular complexity. The nuclear ensemble method has previously been successfully applied to simulating the electronic absorption spectra of other atmospherically relevant systems. …”
Section: Introductionmentioning
confidence: 99%
“…Each trajectory can stochastically switch between electronic states in regions of strong NA coupling. While FSSH has known shortcomings (including overcoherence and neglect of tunneling and interference effects), it often provides an accurate and scalable method that is now widely used to explore photochemical and photophysical phenomena, also for atmospheric chemistry. Given that FSSH typically has a sub-femtosecond integration time step, pushing the simulation into the nanosecond regime necessitates compromises with respect to the electronic structure method and number of trajectories. It has been suggested that this bottleneck might be overcome through machine-learned energies and couplings …”
Section: Introductionmentioning
confidence: 99%